2022
DOI: 10.3390/polym14071439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Starch Coating Embedded with Silver Nanoparticles on Strawberry Storage Time

Abstract: The strawberry has a very short postharvest life due to its fast softening and decomposition. The goal of this research is to see how well a starch-silver nanoparticle (St-AgNPs) coating affects the physical, chemical, and microbiological qualities of strawberries during postharvest life. Additionally, the effect of washing with running water on silver concentration in coated strawberry fruit was studied by an inductively coupled plasma-optical emission spectrometer (ICP-OES). Furthermore, the shelf-life perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…0.02% and 0.03% as compared to 0.04% and 0.05% of AgNPs (Fig 15). Similar trends were obtained by researchers who used 0.01% AgNPs with Polyvinyl pyrolidone (PVP) solution and used these nanoparticle coatings in packaging of Rutab dates to enhance their shelf life for 30 days at 12˚C in Italy [67] and coating of AgNPs to maintain the post-harvest quality in strawberry by increasing its shelf life for 16 days [68]. The researchers explained the role of AgNPs in reduction of respiration or evaporation that increased the shelf life of treated banana samples by maintaining the moisture level in fruits and vegetables [63,67].…”
Section: Plos Onesupporting
confidence: 73%
See 1 more Smart Citation
“…0.02% and 0.03% as compared to 0.04% and 0.05% of AgNPs (Fig 15). Similar trends were obtained by researchers who used 0.01% AgNPs with Polyvinyl pyrolidone (PVP) solution and used these nanoparticle coatings in packaging of Rutab dates to enhance their shelf life for 30 days at 12˚C in Italy [67] and coating of AgNPs to maintain the post-harvest quality in strawberry by increasing its shelf life for 16 days [68]. The researchers explained the role of AgNPs in reduction of respiration or evaporation that increased the shelf life of treated banana samples by maintaining the moisture level in fruits and vegetables [63,67].…”
Section: Plos Onesupporting
confidence: 73%
“…So, the silver nano-coating may reduce the fruit respiration rate and slow down the consumption of acid content during the physiological and metabolic processes of fruit. As a result, the AgNPs may prolong the ripeness of banana after harvesting and increase its shelf life [58,68].…”
Section: Plos Onementioning
confidence: 99%
“…The greater acidity drop in the uncoated strawberries could be attributed to the use of acids as precursors for metabolism throughout preservation. Nano-coatings could inhibit the respiration of samples and slow down the consumption of acid in the physiological metabolic activities of fruits, thus effectively slowing down the downward trend of titratable acid and extending the shelf-life of the fruits [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, chitosan inhibits the cell's protein synthesis by altering the DNA of microorganisms (Goy et al, 2009). Nano-sized silver particles are widely used in medical applications and implants due to their broadspectrum antimicrobial activity and non-toxicity to bacteria, fungi and viruses (Dakal et al, 2016;Fahmy et al, 2017;Taha et al, 2022;Yin et al, 2020;Bruna et al, 2021). Studies have demonstrated that silver alters and inhibits the effects of cellular enzymes and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that silver alters and inhibits the effects of cellular enzymes and DNA. It has been determined that Ag (I) ions bind to and neutralize electron-carrying compounds such as thiols, carboxylates, amides and imidazoles found in the enzyme and DNA structures of microorganisms (Taha et al, 2022). Ascorbic acid (AA) is used as an antioxidant due to its ability to retain oxygen.…”
Section: Introductionmentioning
confidence: 99%